Economy and Environment, do They Always Have to Be Opposites?: Investigating The Environmental Kuznets Curve Theory in Indonesia Using an Econometrical Model (ARDL) - Farazilah, Nada Asria (Syntax Literate, 2025)
In debates related to sustainable development, the issue of the potential conflict between the economy and the environment often comes to the forefront. Indonesia stands out as a major economic player in Southeast Asia; however, it ranks as the 9th highest emitter of CO2 globally. This study seeks to verify the validity of the Environmental Kuznets Curve in Indonesia, demonstrating that high economic growth leads to improvements in environmental quality. This study employs carbon emissions as the dependent variable, which describes the environment, and GDP per capita as a proxy for economic variables. It also incorporates additional control variables such as gross fixed capital formation as domestic investment, renewable energy, and population density. This study used Autoregressive Distributed Lag (ARDL) techniques as data retrieved from World Bank which covered the years 1960–2022. According to the study’s finding EKC hypothesis does not exist. GDP has significant impact to increase carbon emissions, Whereas, domestic investment and the consumption of renewable energy evoke the significant impact on lowering carbon emissions. Furthermore, population density tends to elevate the carbon emissions. These findings indicate that the Indonesian government should transition to avoid environmental damage while promoting economic development.